2022
DOI: 10.21037/atm-21-6367
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for 2018 FIGO stages IB1, IB2, and IIA1 cervical cancer: a large multicenter study

Abstract: Background: Nomograms are predictive tools widely used for estimating cancer prognosis. We aimed to develop/validate a nomogram to predict the postsurgical 5-year overall survival (OS) and disease-free survival (DFS) probability for patients with stages IB1, IB2, and IIA1 cervical cancer [2018 International Federation of Gynecology and Obstetrics (FIGO 2018)]. Methods: We retrospectively enrolled cervical cancer patients at 47 hospitals with stages IB1, IB2, and IIA1 disease from the Clinical Diagnosis and Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Another study [ 50 ] in 2020 found that pretreatment albumin to fibrinogen ratio was significantly related to lymph node metastasis, depth of stromal infiltration, etc. Many studies focused on prediction for survival outcomes or a single PRF of cervical cancer based on clinical factors [ 51 , 52 , 53 ] and/or radiomic parameters [ 54 , 55 ]. However, no studies have made an attempt to predict three PRFs based on a series of clinically readily available blood markers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 50 ] in 2020 found that pretreatment albumin to fibrinogen ratio was significantly related to lymph node metastasis, depth of stromal infiltration, etc. Many studies focused on prediction for survival outcomes or a single PRF of cervical cancer based on clinical factors [ 51 , 52 , 53 ] and/or radiomic parameters [ 54 , 55 ]. However, no studies have made an attempt to predict three PRFs based on a series of clinically readily available blood markers.…”
Section: Discussionmentioning
confidence: 99%